(untitled) (Homoeopathy for All, 2025)
Normal bone is composed of protein, collagen, and calcium, all of which give bone its strength. Bone has hard and solid outer shell surrounding the connecting plates and rods of bones within which lies the bone marrow, internally they are soft and spongy and thus bones are light, strong and flexible. Good health of the individual is mostly depend on strong bone and healthy skeletal makeup. There are totally 206 bones present in human body which are exquisitely and perfectly placed to keep skeleton in appropriate shape and in a healthy manner. Osteoporosis literally leads to abnormally porous bone that is compressible, like a sponge. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.